The impact of central bank digital currency on central bank profitability, risk-taking and capital - Ulrich Bindseil; Marco Marrazzo; Stephan Sauer (European Central Bank (ECB), 2024)
As digital payments become increasingly popular, many central banks are looking into the issuance of retail central bank digital currency (CBDC) as a new central bank monetary liability in addition to banknotes and commercial bank reserves. CBDC will have broadly the same balance sheet and profit implications as the issuance of banknotes. While the decision to issue CBDC is often thought to likely increase the size of central banks' balance sheets, the net impact of digitalisation on balance sheet size could also be negative, as the number of banknotes in circulation may decline and CBDC's design features could limit its take-up as a store of value. We use scenario analyses to illustrate the key drivers of the impact of CBDC on central bank profitability, with the part of CBDC that does not derive from an exchange of banknotes being an important factor. The financial risk implications of CBDC for central banks can be managed via well-established frameworks and relate primarily to the impact on balance sheet size and asset composition. The paper concludes with a discussion on how the profit and risk channels affect central bank capital.
Keywords: E58; 330; central bank digital currency; central bank capital; financial risk management; seigniorage; digital money; central bank; electronic money; financial risk; profitability